Psoas muscle volume is correlated with sexual activity and erectile dysfunction among patients with localised prostate cancer. (23rd June 2019) - Kashiwagi, Eiji; Imada, Kenjiro; Monji, Keisuke; Takeuchi, Ario; Shiota, Masaki; Inokuchi, Junichi; Tatsugami, Katsunori; Eto, Masatoshi
Abstract: Several endocrinological and physical activities orchestrate men's sexual activities. To determine whether body composition calculated by computed tomography measurements is useful for estimating sexual function, we evaluated sexual function of localised prostate cancer patients using the Sexual Health Inventory for Men score, an original questionnaire, and computed tomography and magnetic resonance imaging. The imaging was performed to determine body composition, particularly the psoas muscle. Univariate and multivariate analyses were performed to identify factors affecting sexual activity. The multivariate analysis showed that the volume of the psoas muscle was significantly correlated with sexual activity (odds ratio [95% confidence interval]) (2.507 [1.029–6.109], p  = 0.043) and erectile dysfunction (0.261 [0.098–0.692], p  = 0.006). We concluded that the psoas muscle is an important predictor of sexual activity and erectile function.